Company’s Supply Chain Strategy in Internal Factors to Predict Capital Structure and Profitability on Manufacturing Sector - Evelyn Wijaya; Nur Fadjrih Asyik; Budiyanto Budiyanto; Teddy Chandra; Priyono Priyono (International Journal of Supply Chain Management, 2020)
Abstract- Supply chain is crucial in the current highly competitive and fast-changing business environment, in which the optimisation of all resources matters, creating an ef?cient. Capital structure based on the supply chain strategy is one of the important decisions for financial managers who are able to describe the overall cost of capital and have an impact on increasing the profitability of the company. The aim of this research was (1) to analyze the influence of internal factors including company size and tangibility on capital structure and profitability and (2) to analyze the influence of internal advertising factors on profitability. This study’s samples were 117 manufacturing companies in Indonesia Stock Exchange for period 2010-2016. The data were analyzed by using path analysis with SmartPLS 3.0. The results of the research stated that firm size had a significant effect on capital structure and profitability, tangibility did not have a significant effect on capital structure but had a significant effect on profitability. Meanwhile, advertising did not have a significant effect on profitability. Furthermore, there is a positive influence between capital structure and profitability. This result is in accordance with signalling theory which states that the addition of corporate debt supported by the achievement of high corporate profits will be a positive signal for investors.